The effect of word imagery on priming effect under a preconscious condition: An fMRI study. Issue 9 (1st April 2014) - Lee, Jong‐Sun; Choi, Jeewook; Yoo, Jae Hyun; Kim, Minjung; Lee, Seungbok; Kim, Ji‐Woong; Jeong, Bumseok
Abstract Semantic priming is affected by the degree of association and how readily a word is imagined. In the association effect, activity in the perisylvian structures including the bilateral inferior frontal gyrus, the left middle temporal gyrus, and the supramarginal gyrus was correlated. However, little is known about the brain regions related to the effect of imagery word under the preconscious condition. Forty word pairs for high (HA)‐, low (LA)‐, and nonassociation (NA), nonword (NW) conditions were presented. Each 40 association word pairs (HA and LA) included 20 high (HI) and 20 low (LI) imagery prime stimuli, using a visually presented lexical decision task. A trial consisted of 30 ms prime, 30 ms mask, 500 ms probe, and 2–8 s stimulus onset asynchrony. Brain activation was measured using functional magnetic resonance imaging during word discrimination. Behavioral data indicated that the shortest response time (RT) was given for HA words, followed by LA and NA, and NW showed the longest RT (P < 0.01). RT was faster in HI than LI within HA, but not LA conditions (P < 0.01). Functional neuroimaging showed that differential brain regions for high imagery (HI) and low imagery (LI) words within low prime‐target word association were observed in the left precuneus, left posterior cingulate gyrus, and right cuneal cortex. The present findings demonstrate that the effect of the degree of imagery on semantic priming occurs during the early stage of language processing, indicating an "automatic imagery priming effect." Our paradigm may be useful to explore semantic deficit related to imagery in various psychiatric disorders. Hum Brain Mapp 35:4795–4804, 2014. © 2014 The Authors. Human Brain Mapping Published by Wiley Periodicals, Inc.